Tecnologia do ensino aplicada à educação a distância: uma avaliação - Ribeiro, Gisele de Lima Fernandes (2014)
Skinner, in the book The Techonology of Teaching (1968), introduces guiding principles for a teaching program that leads to a behavior changing of the student towards the expected objectives. In order to analyze how the principles, established in the late sixties and still studied nowadays by behavior analysts, could contribute to distance education, a type of teaching that although it is not recent, has been developing a lot lately, this study, based on the investigation of a teaching method applied to an online subject of a regular undergraduate course, proposes a teaching method for distance education based on the principles of the teaching program proposed by Skinner. This study was developed in distinct phases. In the first one, based on the description of the teaching methodology of the subject taught through distance education, there was the detailing of its constituents elements, evaluation activities and the suggested path for their achievement. The comparison between the teaching proposal and the implementation of one of its teaching units was performed in the second phase of the study. In the following stage, the teaching proposal was analyzed according to the principles considered by Skinner as necessary for the planning of contingency which leads to the behavior changing of the student towards the expected objectives. In the fourth phase, the results were evaluated from the point of view of the students learning and in the fifth phase, the relation between these results and the specific characteristics of the unit program were analyzed. Finally, in the sixth phase, proposals for adjusting the contingencies in the teaching unit analyzed were made, covering the principles defended by Skinner for the teaching programming. Alternative proposals were made considering the institution possible limitations as well as any legislation impossibilities. Based on the results obtained, it is discussed that the application of the principles proposed by Skinner 50 years ago for distance education demonstrates the usefulness and the relevance of these principles for the teaching planning and that they can be effectively applied to this teaching type. It is also discussed that the technological resources, commonly used in this type of education, contribute to the application of what Skinner devised in the late sixties